Gasification of cashew nut shells for thermal application in local food processing factory - Tippayawong N. (2017)
Cashew nut shells are high energy content residues from cashew nut processing. It can potentially replace fuelwood for thermal application in a factory. However, direct combustion of cashew nut shells was troublesome due to low efficiency and high smoke emission. Alternative thermal conversion of cashew nut shells should be used instead. In this work, a gasifier system was designed, built, and installed at a local cashew nut processing factory. Cashew nut shells were converted to producer gas in the downdraft fixed-bed gasifier. The gaseous fuel was then fed to a burner to supply hot water for the factory. From the results obtained, cashew nut shells were successfully used as feedstock in a gasifier. Satisfactory operation was obtained. Gasification of cashew nut shells could provide required thermal input, with clean fuel to the local food processing factory. Preliminary economic analysis showed that the factory can save around $150 a month, with simple period to positive cash flow of less than a year. © 2010 International Energy Initiative.